Vegetation structure, aboveground biomass, and carbon storage of wono¸ a local forest management in Gunungkidul, Yogyakarta, Indonesia, across three geomorphological zones - Tohirin Tohirin; Priyono Suryanto; Ronggo Sadono (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Tohirin, Suryanto P, Sadono R. 2021. Vegetation structure, aboveground biomass, and carbon storage of wono¸ local forest management in Gunungkidul, Yogyakarta, Indonesia, across three geomorphological zones. Biodiversitas 22: 3207-3218. Wono is local community-based forest management in Gunungkidul District, Yogyakarta. This land use has the potential to reduce carbon dioxide emissions through their carbon sequestration capacity as well as to produce renewable energy sources through wood biomass for charcoal and wood pellet. Since Gunungkidul is unique in terms of geomorphological characteristics, study on the vegetation structure, biomass estimation, and carbon storage of wono across geomorphological zones are important. Therefore, this study describes the vegetation structure of wono in three geomorphological zones of Gunungkidul District, as well as estimates the aboveground living biomass (AGB) and aboveground living carbon storage (AGC). The quadratic sampling technique was used to collect data for vegetation analysis with the size of the plots were 20 m x 20 m, 10 m x 10 m, 5 m x 5 m, and 2 m x 2 m for trees, poles, saplings, and seedlings, respectively. A total of 32 plots were established, consisting of 18 plots in Nglanggeran Village, 12 plots in Dengok Village, and six plots in Girisekar Village, each village representing geomorphological zones of Batur Agung, Ledok Wonosari, and Pegunungan Seribu, respectively. The AGB was performed non-destructively and estimated using referenced allometric equations. Furthermore, the AGC was calculated using a conversion factor of 0.47 from the obtained AGB. The results showed that the identified species at wono in Batur Agung, Ledok Wonosari, and Pegunungan Seribu zones were 13, 7, and 8, respectively. Swietenia macrophylla had the highest important value index (IVI) of 185.22% in the Batur Agung zone, while Tectona grandis was the most important species in both the Ledok Wonosari and Pegunungan Seribu zones with IVI= 238.27% and 178.60%, respectively. The biodiversity in these three zones was very low in terms of species diversity (H' < 2) and species richness (R1 < 3.4). The estimated AGB and calculated AGC in the Batur Agung, Ledok Wonosari, and Pegunungan Seribu zones were 210.96 ton ha-1 and 99.15 ton C ha-1, 73.58 ton ha-1 and 34.58 ton C ha-1, and 57.92 ton ha-1 and 27.22 ton C ha-1, respectively.